Solution of HARQ timing collision in dynamic TDD technology - Gang ZHANG; Shixiao LIU; Wei JIANG; Heng HU (Dianxin kexue)
Dynamic TDD system was introduced to satisfy the increasing business requirement and improve the sys-tem performance.In the dynamic TDD system,the frame configuration can be changed based on the traffic load.Since some subframes may change their transmission direction after reconfiguration,some HARQ process will be-come useless.In order to solve the collision problem of HARQ timing in dynamic TDD system,hybrid automatic re-transmission scheme based on transitional radio frame was proposed.A radio frame will be added after the reconfi-guration point.HARQ timing can transit to the reconfigured frame in a simple way with few collisions.Performance evaluation was provided to show the effectiveness of the scheme.Using the proposed scheme can bring benefits to the system average throughput and improve the system resource utilization rate.